DETECTION OF SENTINEL LYMPH NODES IN ORGAN-PRESERVING TREATMENT FOR INVASIVE CERVICAL CANCER - A. L. Chernyshova; L. A. Kolomiets; B. I. Chernov; I. G. Sinilkin (Сибирский онкологический журнал)
For early stages of cervical cancer, minimally invasive surgery leads to more beneficial outcomes compared to results of more extensive surgery. In this connection, the studies that focus on the assessment of the efficacy of organ-preserving and functionally-sparing approaches to surgical treatment of cervical cancer are of great significance. Sentinel lymph node (SLN) biopsy is the preferred method for assessing pelvic nodal basin status in patients with early stage cervical cancer. The concept of sentinel lymph nodes is especially relevant in cases where the status of lymph nodes is the most important factor in the expediency of performing organ-preserving or adjuvant treatment. The review highlights the problems of the clinical significance of SLN biopsy in detection of metastases that could not be detected using traditional techniques. The diagnostic  effectiveness of various routes of tracer injection for SLN visualization was assessed. The comparative results of the use of radiopharmaceuticals used either alone or in combination with blue dye for identification of SLNs were shown. The innovative technique for SLN detection were presented.